2023
DOI: 10.3390/ijms241210320
|View full text |Cite
|
Sign up to set email alerts
|

Basophil Characteristics as a Marker of the Pathogenesis of Chronic Spontaneous Urticaria in Relation to the Coagulation and Complement Systems

Abstract: Chronic spontaneous urticaria (CSU) is a common skin disorder characterized by daily or almost daily recurring skin edema and flare with itch and pruritus anywhere on the body for more than 6 weeks. Although basophil- and mast cell-released inflammatory mediators, such as histamine, play important roles in the pathogenesis of CSU, the detailed underlying mechanism is not clear. Since several auto-antibodies, IgGs which recognize IgE or the high-affinity IgE receptor (FcεRI) and IgEs against other self-antigens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…Our previous studies suggest that histamine may play both in an early step in inducing tissue factor expression on vascular endothelial cells and a late step in inducing plasma extravasation via the increase of vascular permeability (Fig. 1 ) 25 . However, its role in the cascade, especially in the early step, may be substituted to some extent by other factors, such as LPS and cytokines.…”
Section: Discussionmentioning
confidence: 95%
“…Our previous studies suggest that histamine may play both in an early step in inducing tissue factor expression on vascular endothelial cells and a late step in inducing plasma extravasation via the increase of vascular permeability (Fig. 1 ) 25 . However, its role in the cascade, especially in the early step, may be substituted to some extent by other factors, such as LPS and cytokines.…”
Section: Discussionmentioning
confidence: 95%
“…The ratio of basophils in leukocytes and the number of basophils in the peripheral blood of patients with CSU are significantly low compared to healthy donors and patients with atopic dermatitis. Yanase et al showed in their review that not only basophil-associated biomarkers, such as plasma histamine and total IgE levels but also cytomarkers, such as basophil numbers in peripheral blood, the ratio in leukocytes, responsiveness to stimuli, expression of receptors and location, may also be useful in determining the disease activity [ 39 ]. Also, Poddighe and Vangelista’s review mentions that an overall analysis of three pivotal trials (conducted by Gericke et al, Metz et al, and Akdogan et al) aiming to assess the safety and efficacy of omalizumab in patients with CSU confirmed the increase of circulating basophils in patients treated with omalizumab at the conventional dose [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cells similar to mast cells are basophils, which are slightly smaller in size than MCs (8 µm); their cytoplasm has fewer granules; their granules do not contain tryptase; their cell membrane has no KIT receptor but contains the FcεR1 receptor. Basophil precursors mature in the bone marrow under the influence of Il-3 [4]. The granules stain metachromatically with toluidine blue, safranin, or berberine sulfate.…”
Section: Characteristics Of Mastocytesmentioning
confidence: 99%